Randomized trial on the effect of an oral spleen tyrosine kinase inhibitor in the treatment of IgA nephropathy - Tam, Frederick W. K.; Tumlin, James; Barratt, Jonathan; Rovin, Brad H.; Roberts, Ian S. D.; Roufosse, Candice; Cook, H. Terence; Bhangal, Gurjeet; Brown, Alison L.; Busch, Martin; Dudhiya, Fayaz; Duliege, Anne-Marie; et al. (Kidney international. Reports, 2023)
Introduction - We reported increased spleen tyrosine kinase (SYK) expression in kidney biopsies of patients with IgA nephropathy (IgAN) and that inhibition of SYK reduces inflammatory cytokines production from IgA stimulated mesangial cells. - Methods - This study was a double-blind, randomized, placebo-controlled phase 2 trial of fostamatinib (an oral SYK inhibitor) in 76 patients with IgAN. Patients were randomized to receive placebo, fostamatinib at 100 mg or 150 mg twice daily for 24 weeks on top of maximum tolerated dose of renin-angiotensin system inhibitors. The primary end point was reduction of proteinuria. Secondary end points included change from baseline in estimated glomerular filtration rate (eGFR) and kidney histology. - Results - Although we could not detect significant reduction in proteinuria with fostamatinib overall, in a predetermined subgroup analysis, there was a trend for dose-dependent reduction in median proteinuria (from baseline to 24 weeks by 14%, 27%, and 36% in the placebo, fostamatinib 100 mg, and 150 mg groups, respectively) in patients with baseline urinary protein-to-creatinine ratios (UPCR) more than 1000 mg/g. Kidney function (eGFR) remained stable in all groups. Fostamatinib was well-tolerated. Side effects included diarrhea, hypertension, and increased liver enzymes. Thirty-nine patients underwent repeat biopsy showing reductions in SYK staining associated with therapy at low dose (−1.5 vs. 1.7 SYK+ cells/glomerulus in the placebo group, P < 0.05). - Conclusions - There was a trend toward reduction in proteinuria with fostamatinib in a predefined analysis of high risk patients with IgAN despite maximal care, as defined by baseline UPCR greater than 1000 mg/g. Further study may be warranted.
Online verfügbar 30 September 2023, Version des Artikels 4 December 2023
Gesehen am 15.04.2024